Severe cardiovascular system involvement in a patient with Marfan’s syndrome - O. S. Groznova (Rossijskij Vestnik Perinatologii i Pediatrii, 2016)
The given clinical case of a 14-year-old child with Marfan’s syndrome demonstrates the early severe cardiovascular system diseases, such as dilated cardiomyopathy and aortic root dilatation, that required surgical treatment when he was 9 years old, and grades 2 and 3 insufficiency of the mitral and aortic valves, respectively. The paper presents the modern view of the involvement of the heart and vessels in Marfan’s syndrome (cardiomyopathy as a new sign of the disease, arterial dissection). It shows new possibilities for treating cardiovascular disorders in children with this disease, such as pathogenetic therapy with losartan, anti-transforming growth factor-β antibodies.